2016
DOI: 10.1016/j.jid.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Canine Model of Atopic Dermatitis to Investigate the Efficacy of a CCR4 Antagonist in Allergen-Induced Skin Inflammation in a Randomized Study

Abstract: Atopic dermatitis (AD) is an inflammatory skin disease characterized by infiltration of skin homing lymphocytes into the dermis. Most of these lymphocytes express the chemokine receptor CCR4, and the frequency of blood CCR4(+) lymphocytes correlates with AD disease severity. Canine AD is a pruritic inflammatory condition that shows many features of the human disease, including CCR4 overexpression. Therefore, we tested a potent selective CCR4 antagonist in an allergen challenge model of canine AD, both clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…CCL17 promotes the Th2 response via CCR4. The number of CCR4-expressing lymphocytes in serum is correlated with AD severity, the serum IgE level and the blood eosinophil count [180,181]. Furthermore, increased CCL17 levels in cord blood are associated with the development of infantile AD [182].…”
Section: Immunological Abnormalitiesmentioning
confidence: 99%
“…CCL17 promotes the Th2 response via CCR4. The number of CCR4-expressing lymphocytes in serum is correlated with AD severity, the serum IgE level and the blood eosinophil count [180,181]. Furthermore, increased CCL17 levels in cord blood are associated with the development of infantile AD [182].…”
Section: Immunological Abnormalitiesmentioning
confidence: 99%
“…Previous studies have shown that the CCL17-CCR4 axis is associated with immunologically mediated diseases, such as systemic lupus erythematosus (SLE), atopic dermatitis, and asthma. [11][12][13] In addition, there is evidence to support that CCR4 is a necessary component of skin-specific lymphocyte trafficking. 9,10 Previous studies reported overexpression of CCL17 and CCR4 in OLP tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Ten atopic beagles previously sensitized epicutaneously to both environmental and food allergens and housed in a controlled allergen environment were used . There had been no prior exposure to Bermuda grass allergen.…”
Section: Methodsmentioning
confidence: 99%
“…Our primary aim was to investigate if oclacitinib affected epicutaneous sensitization using a placebo‐controlled prospective design. A colony of atopic beagle dogs was used in a controlled environment with standardized allergen exposure . The second aim was to investigate the effect of oclacitinib on skin permeability by measuring transepidermal water loss (TEWL).…”
Section: Introductionmentioning
confidence: 99%